Meningkatkan Hasil Belajar Pendidikan Agama Katolik Melalui Model Problem Based Learning Kelas VII SMP Mardi Waluya Bogor - Yustina Piarahmawati; FX. Sugiyana; Veronica Nurhayati (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve students' learning outcomes in Catholic Religious Education (PAK) for seventh-grade students at SMP Mardi Waluya Bogor through the implementation of the Problem Based Learning (PBL) model. The research utilized Classroom Action Research (CAR) conducted in two cycles, each involving planning, implementation, observation, and reflection stages. The results showed improvements in students' cognitive, affective, and psychomotor aspects. In the cognitive aspect, students categorized as proficient increased by 26% from the pre-action phase to the second cycle. Meanwhile, in the affective aspect, especially in critical thinking and cooperation abilities, there was a 4% increase in the proficient category and a 26% increase in the competent category. The psychomotor aspect saw the most significant improvement, with the proficient category rising by 43%. In addition to enhancing content understanding, the PBL model also successfully developed essential skills such as leadership, collaboration, and creativity. Based on these findings, the implementation of PBL has proven effective in improving students' learning outcomes and equipping them with critical thinking and relevant skills to face future challenges.